Exploring factors influencing the uptake of kangaroo mother care: key informant interviews with parents - Wai Cheng Foong; Siew Cheng Foong; Jacqueline J. Ho; Divya Gautam; Jen Jen Leong; Pek Yong Tan; Mehala Baskaran (BMC, 2023)
Abstract Background The updated World Health Organization (WHO) guideline recommends immediate kangaroo mother care (KMC) for all infants, particularly those born preterm. However, its uptake and sustainability have been unsatisfactory. Therefore, we aimed to gain deeper insight into factors influencing the uptake of KMC practice in our setting, and thereby identify possible solutions for the development of relevant interventions to improve its adoption and make KMC a routine practice for all infants. Methods Using the Triandis model of social behaviour as our framework, we conducted key informant interviews with parents and healthcare providers. Trained interviewers conducted interviews with nine parents, recruited via purposive sampling. These parents were parents of preterm infants who had been introduced to KMC. Data was transcribed and analysed based on Triandis' Theory of Interpersonal Behaviour. This paper only reports the results of the parent interviews. Results Major findings were how positive feelings like warmth and contentment, the sense of parenthood with KMC, the benefits of KMC for their infant and parents being enablers for KMC uptake. Conversely, the lack of KMC awareness, the initial negative feelings such as fear, uncertainty and embarrassment, the prioritization of time for milk expression, overcrowding in the ward, lack of space and privacy, limited visiting hours, lack of support and poor communication resulting in misapprehension about KMC were major barriers. Conclusion A deeper understanding of the factors influencing the uptake of KMC using the Triandis behavioural model provided a way forward to help improve its uptake and sustainability in our settings. Trial registration This study was registered with the National Medical Research Registry (NMRR-17-2984-39191).